2021
DOI: 10.4103/ijem.ijem_246_21
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and its Determinants in Patients with Diabetes Mellitus from Two Health Institutions of Sub-himalayan Region of India

Abstract: Background: Diabetes mellitus (DM) causes serious deterioration in general quality of life (QoL) mainly affecting the health-related quality of life (HRQOL). Routine assessment of QoL improves communication with the patient, helps to predict treatment response, and supports clinical decision-making. QoL can predict an individual's capacity to manage the disease and maintain long-term health and wellbeing. Aims: To find out the QoL and its socio-demographic, anthropometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 43 publications
2
10
0
Order By: Relevance
“…12 Similarly, in a study conducted by Gupta J et al in Bilaspur, Himachal Pradesh in the year 2018 it was found thar lower family income predicted poor health related quality of life among diabetic subjects . 14 Similar to the present study, in a study conducted by Alsuwayt S et al in Riyadh, Saudi Arabia in 2019 it was found that the diabetic subjects belonging to low socioeconomic status had a poor quality of life compared to those belonging to the higher socioeconomic status. 22 In the present study, overall quality of life and general health score was higher in diabetic subjects with duration of disease <2 years as compared to diabetic subjects with duration ≥2 years.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…12 Similarly, in a study conducted by Gupta J et al in Bilaspur, Himachal Pradesh in the year 2018 it was found thar lower family income predicted poor health related quality of life among diabetic subjects . 14 Similar to the present study, in a study conducted by Alsuwayt S et al in Riyadh, Saudi Arabia in 2019 it was found that the diabetic subjects belonging to low socioeconomic status had a poor quality of life compared to those belonging to the higher socioeconomic status. 22 In the present study, overall quality of life and general health score was higher in diabetic subjects with duration of disease <2 years as compared to diabetic subjects with duration ≥2 years.…”
Section: Discussionsupporting
confidence: 89%
“…13 Gupta J et al conduct-ed a cross-sectional study among 217 diabetic subjects in the year 2014-2018 in Bilaspur, Himachal Pradesh and it was observed that approximately 50% of the participants did not have a very good quality of life. 14 In the current study, mean quality of life scores was significantly lower in diabetic subjects in the domain of physical health (47.48), psychological domain (35.64) and domain of social relationships (53.74). However environmental domain score was nearly equal in both diabetic and healthy subjects (46.99 and 48.44 respectively).…”
Section: Discussionmentioning
confidence: 43%
“…A study conducted in urban Puducherry, South India reported high satisfaction levels of about 70% with the health care services received and there was no significant difference in the level of satisfaction between government and private health facility ( 16 ). In another study conducted at two centers in the sub-Himalayan region of North India, 70% of patients indicated they were moderately (14%) or highly satisfied (56%) with diabetes treatment, with no significant difference by treatment setting ( 17 ). Our survey results indicating high satisfaction level with both the MC (public setting) and the private setting are consistent with the findings in these earlier studies.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the important research done in coming years include research on medical ethics ( Subramanian et al, 2013 ), a framework for the evaluation of medical quality ( Heidari Gorji & Farooquie, 2013 ), utilization of healthcare facilities ( Tavashi & Naik, 2014 ) and non-complaining behavior of inpatients ( Khadir & Swamynathan, 2014 ). Further, research also includes a study on service quality ( Sathish et al, 2018 ), the effect on the satisfaction of the rural population ( Gupta et al, 2021 ), the effect of telemedicine ( Li et al, 2020 ), patient satisfaction with day-care ( Dwivedi et al, 2020 ), patients satisfaction with healthcare, factors affecting the satisfaction of patients ( Kaur et al, 2020 ), satisfaction with the medical tourism industry ( Datta, 2020 ), family-centered care ( Sarin & Maria, 2019 ) and renewable insurance policy ( Ahire & Rishipathak, 2018 ). The aforementioned research studies mainly include satisfaction with healthcare service providers, various medical care, and programs of healthcare.…”
Section: Literature Reviewmentioning
confidence: 99%